Mitigation of Emergent Bacterial Pathogens Using Pseudomonas syringae pv. actinidiae as a Case Study—From Orchard to Gene and Everything in Between - Nunes da Silva, Marta; Santos, Miguel G.; Vasconcelos, Marta W.; Carvalho, Susana M. P. (Crops, 2022)
Globalization propelled human migration and commercial exchanges at the global level, but woefully led to the introduction of non-indigenous organisms into several agroecological systems. These include pathogenic bacteria with devastating consequences for numerous crops of agronomical importance for food production worldwide. In the last decade, research efforts have focused on these noxious organisms, aiming to understand their evolutionary processes, degree of pathogenicity, and mitigation strategies, which have allowed stakeholders and policymakers to develop evidence-based regulatory norms to improve management practices and minimize production losses. One of these cases is the bacterium Pseudomonas syringae pv. actinidiae (Psa), the causal agent of the kiwifruit bacterial canker, which has been causing drastic production losses and added costs related to orchard management in the kiwifruit industry. Although Psa is presently considered a pandemic pathogen and far from being eradicated, the implementation of strict regulatory norms and the efforts employed by the scientific community allowed the mitigation, to some extent, of its negative impacts through an integrated pest management approach. This included implementing directive guidelines, modifying cultural practices, and searching for sources of plant resistance. However, bacterial pathogens often have high spatial and temporal variability, with new strains constantly arising through mutation, recombination, and gene flow, posing constant pressure to agroecosystems. This review aims to critically appraise the efforts developed to mitigate bacterial pathogens of agronomical impact, from orchard management to genome analysis, using Psa as a case study, which could allow a prompter response against emerging pathogens in agroecosystems worldwide.